Combined use of 64-slice computed tomography angiography and gated myocardial perfusion SPECT for the detection of functionally relevant coronary artery stenoses - Hacker, M.; Jakobs, T.; Hack, N.; Nikolaou, K.; Becker, C.; von Ziegler, F.; Knez, A.; König, A.; Klauss, V.; Tiling, R. (Nuklearmedizin - NuclearMedicine, 2007)
Aim: In patients with stable angina pectoris both morphological and functional information about the coronary artery tree should be present before revascularization therapy is performed. High accuracy was shown for spiral computed tomography (MDCT) angiography acquired with a 64-slice CT scanner compared to invasive coronary angiography (ICA) in detecting „obstructive” coronary artery disease (CAD). Gated myocardial SPECT (MPI) is an established method for the noninvasive assessment of functional significance of coronary stenoses. Aim of the study was to evaluate the combination of 64-slice CT angiography plus MPI in comparison to ICA plus MPI in the detection of hemodynamically relevant coronary artery stenoses in a clinical setting. Patients, methods: 30 patients (63 ± 10.8 years, 23 men) with stable angina (21 with suspected, 9 with known CAD) were investigated. MPI, 64-slice CT angiography and ICA were performed, reversible and fixed perfusion defects were allocated to determining lesions separately for MDCT angiography and ICA. The combination of MDCT angiography plus MPI was compared to the results of ICA plus MPI. Results: Sensitivity, specificity, negative and positive predictive value for the combination of MDCT angiography plus MPI was 85%, 97%, 98% and 79%, respectively, on a vessel-based and 93%, 87%, 93% and 88%, respectively, on a patient-based level. 19 coronary arteries with stenoses ≥50% in both ICA and MDCT angiography showed no ischemia in MPI. Conclusion: The combination of 64-slice CT angiography and gated myocardial SPECT enabled a comprehensive non-invasive view of the anatomical and functional status of the coronary artery tree.
Keywords: Myocardial perfusion SPECT; 64-slice spiral CT angiography; invasive coronary angiography; coronary artery disease; stable angina pectoris